1988
DOI: 10.1073/pnas.85.5.1374
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a second yeast Saccharomyces cerevisiae gene (GPA2) coding for guanine nucleotide-binding regulatory protein: studies on its structure and possible functions.

Abstract: In a previous paper, we demonstrated that a gene coding for a protein homologous to the alpha subunit of mammalian guanine nucleotide-binding regulatory (G) proteins occurs in Saccharomyces cerevisiae. The gene, designated GPA1, encodes a protein (GP1 alpha) of 472 amino acids with a calculated Mr of 54,075. Here we report the isolation of another G-protein-homologous gene, GPA2, which encodes an amino acid sequence of 449 amino acid residues with a Mr of 50,516. The predicted primary structure of the GPA2-enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
158
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(162 citation statements)
references
References 36 publications
4
158
0
Order By: Relevance
“…Gpr1 belongs to the G protein-coupled seven-transmembrane receptor (GPCR) superfamily (Yun et al 1997;Xue et al 1998) and Gpa2 is a member of the heterotrimeric G protein a subunit (G a ) protein family (Nakafuku et al 1988). Addition of glucose to derepressed cells activates Gpr1, which in turn stimulates the exchange of GDP for GTP on Gpa2 (Kraakman et al 1999a).…”
Section: Regulation Of the Camp-pka Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Gpr1 belongs to the G protein-coupled seven-transmembrane receptor (GPCR) superfamily (Yun et al 1997;Xue et al 1998) and Gpa2 is a member of the heterotrimeric G protein a subunit (G a ) protein family (Nakafuku et al 1988). Addition of glucose to derepressed cells activates Gpr1, which in turn stimulates the exchange of GDP for GTP on Gpa2 (Kraakman et al 1999a).…”
Section: Regulation Of the Camp-pka Pathwaymentioning
confidence: 99%
“…This probably ensures that the cAMP-PKA pathway is only fully activated when glucose levels are high enough to switch easily from respiration to fermentation. GTP-bound Gpa2 activates the cAMP-PKA pathway and this is most probably through stimulation of adenylate cyclase (Nakafuku et al 1988;Kubler et al 1997;Lorenz and Heitman 1997;Colombo et al 1998;Rolland et al 2000;Peeters et al 2006). Gpa2 interacts with Rgs2, a member of the family of regulators of G protein signalling (RGS), that negatively regulates the Gpa2-GTP signal by stimulating the intrinsic GTPase activity of Gpa2 (Versele et al 1999).…”
Section: Regulation Of the Camp-pka Pathwaymentioning
confidence: 99%
“…A second yeast G␣ protein, Gpa2, is 45% identical and 60% homologous to Gpa1 but is not required for mating (Nakafuku et al 1988). It has been reported recently that Gpa2 modulates growth and pseudohyphal development by regulating intracellular cAMP levels (Kubler et al 1997;Lorenz & Heitman 1997).…”
Section: G1-deg Confers N-end Rule-dependent Targeting On Gpa2mentioning
confidence: 99%
“…The overexpression of CDC25 product does not markedly stimulate the PI turnover as well as it does not change significatively the intracellular cAMP level ( [12], Frascotti et al, manuscript in preparation). Since Gproteins, different from RAS proteins, are present in yeast [16,17], it can be tentatively suggested that another G-protein may be responsible for the PI turnover in yeast, while RAS1 and RAS2 proteins work normally only on the adenylate cyclase pathway. An 'activating' RAS mutation, like RAS2 vaIl9 which may alter the target specificity of the protein, could originate the observed hyperstimulatory effect.…”
Section: Cdc25 Ras1mentioning
confidence: 99%